SHARIA INVESTMENT FUNDS: IS IT TRULY BOOSTING THE PROFITABILITY OF SHARIA INSURANCE? - Fauzan, Iqbal Zul; Wicaksono, Ahmad Tibrizi Soni (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Sharia insurance revenue has decreased precisely during the COVID-19 pandemic. It is recorded that Sharia insurance has decreased in 2019-2020, decreasing by around 10%. The gross distribution at that time experienced a significant increase. Meanwhile, funds in sharia investments fluctuated in sharia stocks, sukuk, National Sharia Securities (SBSN), sharia mutual funds, and sharia deposits. This research aims to find out which Sharia investment instruments are the most optimal in providing profits to companies, so that they can help companies increase profitability. The research method used in this study is the quantitative method. The population in this study uses all Sharia insurance companies in Indonesia using saturated sampling techniques. The data used in this study is secondary data taken from monthly reports at the OJK (Financial Services Authority), which is then processed into an annual report for 2018-2022. The analysis of this study used the multiple linear regression method with Eviews 13. The study results show that the variables of Sharia stocks partially affect the profitability of Sharia insurance. Then the sukuk variable does not affect the profitability of sharia insurance. As well as SBSN variables, sharia mutual funds and sharia deposits hurt the profitability of sharia insurance. Meanwhile, simultaneously, the variables of sharia stocks, sukuk, SBSN, sharia mutual funds, and sharia deposits affect the profitability of sharia insurance.